Outcomes of mitral valve repair in acute native mitral valve infective endocarditis. (1st August 2019) - El Gabry, Mohamed; Haidari, Zaki; Mourad, Fanar; Nowak, Janine; Tsagakis, Konstantinos; Thielmann, Matthias; Wendt, Daniel; Jakob, Heinz; Shehada, Sharaf-Eldin
Abstract: OBJECTIVES: Mitral valve repair (MVR) is considered the treatment of choice for mitral valve (MV) regurgitation. However, MVR in acute native MV infective endocarditis is technically challenging and not commonly performed. Our goal was to report our outcomes of MVR in acute native MV infective endocarditis. METHODS: Between January 2016 and December 2017, 35 patients presenting with acute native MV infective endocarditis underwent MVR. Primary end points were successful MVR and freedom from recurrent endocarditis. Secondary end point was the postoperative incidence of major adverse events. RESULTS: The mean age was 58 ± 13 years (74% men) and the median logistic EuroSCORE was 17.1%. Twenty patients underwent isolated MVR; the other 15 patients underwent concomitant procedures. MVR was performed with removal of the vegetation (vegectomy), limited resection of the infected tissue, direct closure of the defect, besides annuloplasty in all patients. Mean intensive care and hospital stays were 5 and 17 days, respectively. All-cause mortality was 11% (4/35) at 30 days and a total of 23% (8/35) within a follow-up period of 10 ± 7.7 months. Endocarditis recurred in 2 patients 15 and 8 months after surgery, respectively. Both underwent successful MV re-repair. Follow-up echocardiography indicated none-to-trace, mild or moderate regurgitation in 15, 10 and 2 patients, respectively. CONCLUSIONS: Although MVR in acute native MV infective endocarditis is a complex procedure, it offers a treatment option for such patients with acceptable short-term results. Limited resection in addition to annuloplasty is our preferred method of repair. Nevertheless, long-term results in a larger cohort are still mandatory.